DFT MODELING OF BENZOYL PEROXIDE ADSORPTION ON ?-Cr2O3 (0001) SURFACE - Stashans, A. (2016)
© 2016 World Scientific Publishing CompanyDensity functional theory (DFT) within the generalized gradient approximation (GGA) has been used to investigate possible adsorption configurations of benzoyl peroxide (BPO) molecule on the chromium oxide ((Formula presented.)-Cr2O(Formula presented.) (0001) surface. Two configurations are found to lead to the molecular adsorption with corresponding adsorption energies being equal to (Formula presented.)0.16 and (Formula presented.)0.48(Formula presented.)eV, respectively. Our work describes in detail atomic displacements for both crystalline surface and adsorbate as well as discusses electronic and magnetic properties of the system. The most favorable adsorption case is found when the chemical bond between one of the molecular oxygens and one of the surface Cr atoms has been formed.